2007
DOI: 10.1080/10428190601059837
|View full text |Cite
|
Sign up to set email alerts
|

EBV-related disease following haematopoietic stem cell transplantation with reduced intensity conditioning

Abstract: The use of reduced intensity regimens has decreased early mortality following stem cell transplantation. However, the increased immunosuppression following these protocols results in profound and often prolonged lymphopenia, resulting in an increased incidence of viral reactivation. We and others have observed a high incidence of EBV viraemia and post-transplant lymphoproliferative disease (PTLD) following reduced-intensity conditioning regimens, reflecting the delayed recovery of EBV-specific immunity after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 60 publications
3
41
0
2
Order By: Relevance
“…PTLDs have been well known to be closely associated with EBV infection/reactivation in a setting of decreased host T-cell immune surveillance, particularly the CTLs, leading to an unchecked EBVinfected B-lymphocyte proliferation, acquisition of somatic mutation and eventual malignant lymphoma. 1,[3][4][5][6][7][8][9] This model agrees with the general observation that more than 80% of PTLDs are closely associated with EBV infection/ reactivation and they truly represent an EBV-induced monoclonal or less often polyclonal B-cell or rarely T-cell proliferation. 1 In general, EBVþ cases tend to occur earlier than EBVÀ cases because more potent immunosuppression is often given immediately after the transplantation.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…PTLDs have been well known to be closely associated with EBV infection/reactivation in a setting of decreased host T-cell immune surveillance, particularly the CTLs, leading to an unchecked EBVinfected B-lymphocyte proliferation, acquisition of somatic mutation and eventual malignant lymphoma. 1,[3][4][5][6][7][8][9] This model agrees with the general observation that more than 80% of PTLDs are closely associated with EBV infection/ reactivation and they truly represent an EBV-induced monoclonal or less often polyclonal B-cell or rarely T-cell proliferation. 1 In general, EBVþ cases tend to occur earlier than EBVÀ cases because more potent immunosuppression is often given immediately after the transplantation.…”
supporting
confidence: 74%
“…Despite a very late onset of disease in this patient, extremely high EBV viral copies in our patient's blood and strong expression of viral RNA in the tumor cells indicate that EBV driven B-cell proliferation may occur any time during the course of immunosuppression. [1][2][3][4][5][6][7][8][9][10] Although the exact mechanism of this sudden onset of PTLD so late in the post-transplant course is not clear, persistent chronic GVHD in our patient with recently elevated immunosuppression may have played a critical role in triggering such profound EBV reactivation and eventually lead to the lethal PTLD. 10,11 Furthermore, as in the majority of PTLDs after allogeneic hematopoietic stem cell transplant, all lymphoma cells of the current case were of donor origin.…”
mentioning
confidence: 99%
“…37 In contrast, when no serotherapy is used to T deplete the graft, as in the Seattle FLU/low-dose TBI regimen, the risk of EBV-associated LPD appears low. 17 Likewise, CMV reactivation may also be more frequent following RIC-SCT. 38,39 Data on adenoviral infections after RIC-SCT are conflicting: there does not appear to be any difference in the incidence of adenoviremia between RIC and full intensity conditioning regimens in children 40 but Avivi et al 41 have reported a high incidence of adenovirus-associated disease in adults undergoing RIC-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a high rate of GVHD with 11/14 developing significant aGVHD (mostly grade II) and extensive cGVHD in eight patients, reflecting the use of peripheral blood as the stem cell source and the absence of serotherapy. While this approach may be associated with a lower incidence of viral infections/reactivations, notably EBV than RIC regimens utilizing serotherapy, 17 the incidence of cGVHD is the major obstacle to broader use of this regimen in children with nonmalignant disorders.…”
Section: Primary Immune Deficiencymentioning
confidence: 99%
“…Risk factors for developing EBV-PTLD can be considered as existing pre- 20,24,[33][34][35] or developing post-transplant 7,[34][35][36][37] ( Table 3). Importantly, assessing the risk of EBV-PTLD is dependent on the HSCT context with potentially complex interactions between the primary hematological malignancy, HSCT procedure, source, and other factors.…”
Section: Risk Factors For Ebv-ptldmentioning
confidence: 99%